Reflections for assistance to the LGBTQIA+ public from the perspective of nursing - Castro, Kemely de; Santos, Larissa Christiny Amorim dos; Ribeiro, Wanderson Alves; Fassarella, Bruna Porath Azevedo; Neves, Keila do Carmo; Alves, Ana Lúcia Naves; Amaral, Fernando Salgado do; Paula, Enimar de (Brazilian Journal of Science, 2022)
Although there have been several improvements in the universalization of care in the Unified Health System, prejudice and decriminalization are still present in society as a whole and unfortunately this stigma around the members of the LGTBQIA+ group ends up directly influencing the quality of reception thus disqualifying the service. In this way, people in the group can stop attending health units. This study was motivated by students, with the main objective of reflecting on the assistance and guidance provided to the LGBTQIA+ public in health units and what difficulties faced by this public. This is a descriptive, qualitative study of the reflective analysis type, using the Virtual Health Library (VHL) database, in the following information base: International Health Science Literature (MEDLINE), Scientific Electronic Library Online (SCIELO), Latin American and Caribbean Literature on Health Sciences (LILACS), among others. It is concluded that the health teams are unprepared for the care and reception of this public. The relationship between health services and the homosexual population ends up being harmed when homophobic behavior occurs by the health teams in the service, or when the LGBT population does not feel welcomed or well received by these professionals. Emphasizing the importance of guidance to academics since their formation to form professionals of excellence, providing care with awareness of their importance, without prejudice and taboos.